Study of the trophic and functional organization of fish assemblages in submarine shallow CO2 vents - Mirasole, Alice; VIZZINI, Salvatrice (country:IT, 2014)
Naturally acidified marine ecosystems are currently investigated to evaluate the effects of ocean acidification on species, communities and ecological processes. Among these, submarine shallow CO2 vents represent a sort of natural mesocosms, where at small spatial scales marked gradient of pH are present. The aim of this project is to study the responses of fish assemblages to pH reduction in Mediterranean shallow CO2 vents by using several descriptors such as community structure, trophic organization, chemical characteristics and composition of carbonic structures. Moreover as in CO2 vents concentration and bio-availability of several trace elements, also toxic ones, may increase due to direct input from the vents and/or to peculiar pH and Eh conditions, another aim is the evaluation of trace element bioaccumulation and biomagnification. As scant information is available in the literature on this topic, the results of this research will contribute to bridge the gap to predict the ecological effects of ocean acidification on fishes, a key biological component whose monitoring is relevant not only from the ecological standpoint but also for the economic one and for the implications on human health.